Developing Beru Subdistrict’s Population Data Service Application towards Paperless Office and Good IT Governance - Agustinus Lambertus Suban; Imelda Dua Reja (Indonesian Journal of Multidisciplinary Science, 2022)
Many government and private institutions have begun using information systems to process data and produce quality information. Likewise, the Beru Village Office is a government agency that takes care of population administration as a form of service to the community. Beru Village currently uses a computer as a tool to help with administration related to services. However, making certificates are still manual using Microsoft word.  This gives rise to inefficient time spent in mail creation and data search, and often, there are missing and damaged documents. In terms of storage room efficiency, if all these files are converted into digital form or digitized, then storage space is more effective, duplication costs are more efficient, and the use of paper for documents is minimized, or called a paperless office.  This reduces the environmental impact of the overuse of writing and is cost-effective, time-saving, efficient, and more productive. With a digital format, the dissemination of information becomes more accessible and faster as a manifestation of the paperless offices towards e-document-based institutions. This is why the idea of doing research and developing applications is given. The main shot is to create the implementation of a subdistrict towards a paperless office and Good IT Governance, as well as pilot projects for other agencies in processing data efficiently and entering the digital era.